Impact of Organizational Culture on Employee Performance and Satisfaction: A Study of the Nepalese Banking Sector - Kandel, Arjun Bahadur (Journal of Multidisciplinary Research Advancements, 2025)
This qualitative study investigates the impact of organisational culture on employee performance and satisfaction within the Nepalese banking sector. Based on an analysis of secondary data from annual reports, academic literature, and institutional publications, the research aimed to identify the dominant cultural elements in Nepalese banks and assess their differential effects in public and private institutions. The findings reveal a distinct cultural dichotomy: private-sector banks exhibit performance-driven cultures that yield higher employee productivity but are associated with lower job satisfaction and higher turnover due to job insecurity and high work pressure. Conversely, public-sector banks offer greater job security and satisfaction but exhibit lower productivity, owing to bureaucratic inefficiencies and political interference. The study concludes that a sustainable cultural model must balance performance with employee well-being. It recommends that private banks enhance job security and equitable compensation, whereas public banks should reduce political influence and implement performance-based systems. Future research should employ primary data collection to deepen understanding of the employee experience.